HUBUNGAN INTERAKSI SOSIAL DENGAN MOTIVASI BELAJAR MAHASISWA KEPERAWATAN PROGRAM A SEMESTER VIII FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Febby Jayantari (Coping: Community of Publishing in Nursing, 2014)
Learning is a process effort for someone to acquire a new behavior changes as a whole, as a result of his own experience in the interaction with its environment. Social interaction is a relationship between individual so more, where the behavior of one individual affect, alter, or improve the behavior of another individual otherwise. Student motivation to learn is a situation that encourages students to self and directs her behavior to the goals to be achieved in the following higher education. The purpose of this study was to determine the Relationship Social Interaction with Student Motivation to Learn of Nursing Students Program A Semester VIII Faculty of Medicine Udayana University. This research includes descriptive correlational study using cross-sectional approach. Number of samples was taken from 86 people with sampling technique is the total sampling. Technique of data analysis that is used to test the hypothesis is correlation product moment (p£ 0,05). Result showed the p- value is 0,000, which means p£ 0,05 so Ha is rejected and the value of correlation coefficient of 0, 493 which means that there is a positive relationship direction. The existence of this research can be used as input for the students to improve social interaction with their friends on campus to improve learning motivation in undergoing the process of learning on campus.